Menisdaurin và axit rosmarinic phân lập từ cây cườm rụng hoa dài (Ehretia longiflora Champ., Boraginaceae) - Kiệm và cộng sự, Phan Văn (Vietnam Journal of Chemistry, 2014)
Phytochemical investigation of the stem barks of Ehretia longiflora Champ. afforded menisdaurin and rosmarinic acids. Their chemical structures were identified by combination of 1D-, 2D-NMR, and ESI-MS techniques in comparison with the literature. Menisdaurin acid was isolated for the first time from Ehretia species.